2018
DOI: 10.18632/oncotarget.25413
|View full text |Cite
|
Sign up to set email alerts
|

Triple negative breast cancer subtypes and pathologic complete response rate to neoadjuvant chemotherapy

Abstract: Triple negative breast cancer (TNBC) is a heterogeneous disease with distinct molecular subtypes that differentially respond to chemotherapy and targeted agents. The purpose of this study is to explore the clinical relevance of Lehmann TNBC subtypes by identifying any differences in response to neoadjuvant chemotherapy among them. We determined Lehmann subtypes by gene expression profiling in paraffined pre-treatment tumor biopsies from 125 TNBC patients treated with neoadjuvant anthracyclines and/or taxanes +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 43 publications
10
134
0
3
Order By: Relevance
“…Interestingly, despite the negative results of HER2 testing by IHC and fluorescence in situ hybridization, nearly half of IHC-LAR TNBCs were categorized as the HER2-enriched subtype according to the intrinsic subtyping of breast cancer. This result was consistent with the finding of a previous study by Santonja et al, in which they classified TNBC tumors into intrinsic subtypes and found that 4 out of 10 LAR tumors were categorized as the HER2-enriched subtype [42]. In addition, the IHC-LAR subtype exhibited relatively high levels of ERBB2 mRNA expression and HER2 pathway activity.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, despite the negative results of HER2 testing by IHC and fluorescence in situ hybridization, nearly half of IHC-LAR TNBCs were categorized as the HER2-enriched subtype according to the intrinsic subtyping of breast cancer. This result was consistent with the finding of a previous study by Santonja et al, in which they classified TNBC tumors into intrinsic subtypes and found that 4 out of 10 LAR tumors were categorized as the HER2-enriched subtype [42]. In addition, the IHC-LAR subtype exhibited relatively high levels of ERBB2 mRNA expression and HER2 pathway activity.…”
Section: Discussionsupporting
confidence: 92%
“…For example, tumors of the BL-1 subtype are usually characterized by a higher grade, the highest proliferation rates of Ki-67 expression level (>85%), and upregulation of genes involved in cell proliferation and DNA damage response (such as ATR/BRCA pathway, CHEK1, MSH2, RAD21, and MDC1). Importantly, this subtype is highly sensitive to chemotherapy, with reported pCR up to 50% (32,33). The next is the BL-2 subtype, which has all the above-mentioned features and in addition it shows overexpression of growth factor receptors such as EGFR, NGFR, IGF1R, MET pathway, myoepithelial markers, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The next is the BL-2 subtype, which has all the above-mentioned features and in addition it shows overexpression of growth factor receptors such as EGFR, NGFR, IGF1R, MET pathway, myoepithelial markers, and so on. Clinical studies have shown that the BL-2 subtype is highly resistant to chemotherapy (28,32). The M subtype is associated with the activation of epithelial-mesenchymal transition and cell motility pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic alterations could potentially be exploited as novel treatment targets for TNBC. 18,19 Development of in vitro chip model, composed of a microvessel wall, the extracellular matrix (ECM), and uniformly sized multicellular tumor spheroids (MCTS), used in rapid screening of nanodrugs and delivery systems. Carbon dots (CDs)-based drug delivery system are used to evaluate the real-time monitoring of endothelium and the penetrability into MCTS with a high spatio-temporal resolution.…”
Section: Cancer and Metabolomic Profilingmentioning
confidence: 99%
“…TNBC in Caucasian women was associated with increased pyrimidine synthesis. These metabolic alterations could potentially be exploited as novel treatment targets for TNBC …”
Section: Introductionmentioning
confidence: 99%